William Jefferson Clinton - Heinrichs, Ann (Minneapolis, Minn. : Compass Point Books, 2002)
Discusses the life and accomplishments of the Democrat who was elected president to two successive terms, 1992 and 1996.
The New Democrat -- The early years -- Off to Washington -- Arkansas politics -- A new generation -- The second time around -- Grateful to serve.
Includes bibliographical references and index.
Keywords: Clinton, Bill -- 1946-; Presidents -- United States -- Biography; Presidents